دیوداسی اور پجاری اور فن کا تقابلی جائزہ(فنی وفکری تلازمات کے خصوصی حوالے سے) - Akhtar Ali; Dr. Anwar Ali (Khayaban - خیابان, 2021)
Abstract: Miraji played an integral role in bringing urdu poetry at a par with modern lines while Ahmad Nadeem Qasmi holds a distinctive position among Modern poets. In this treatise, a comparative analysis of Miraji’s poem “Dewdasi aur Pujari” and “Fan” of Ahmad Nadeem Qasmi has been presented. Both the poems share similar blend with regard to artistic achievements and subject matter. The moot point in both the poems is “Dance” where in the feelings of Dewdasi and Raqqasa have been shown. Both the poems are a stark reminder of how the feelings of women are ignored and how the society exploits them. Both the poems have elements of drama, Hindi accent and are erotic based. In short it’s the case of same portraits on different canvases.